PENYULUHAN PELAKSANAAN TEKNIK BIRTH BALL TERHADAP KEMAJUAN PERSALINAN PADA IBU HAMIL TRIMESTER III - Wilda Wahyuni Siregar; Dwi Handayani; Damayanti .; Diah Evawanna Anuhgera; Juni Mariati Simarmata; Raisha Octavariny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
In the first stage of labor, pain is a physiological factor with the cervical dilatation process, uterine muscle hypoxia when it contracts, stretching of the lower uterine segment. Birth ball counseling activities can be carried out to pregnant women in the third trimester. The purpose of this community service is to help relieve the pain and anxiety of the first stage of labor. This can be done in order to maintain and reduce anxiety and stress in third trimester pregnant women. Birth ball can be done with caca sitting on the birth ball, leaning on the ball by kneeling, leaning on the bed with a birth ball. The implementation of this community service lasted for 2 days at the Hamidah Pratama Clinic. This activity begins with checking blood pressure, followed by education about birth balls, the benefits of birth balls, how to use birth balls, along with the provision of leaflets about birth balls, demonstrations on the implementation of birth ball therapy and leaflets on how to use them. . The organizers of the activity also conducted discussions and asked questions to pregnant women in the third trimester related to the implementation of the birth ball which had been socialized. the implementation of counseling conducted on 32 third trimester pregnant women, all respondents experienced a decrease in anxiety and stress and pain in the waist and back and they also already knew that with this technique at the time of delivery it would speed up the first stage process so that the pain experienced would be shorter.